The Predictive Power of Intuitive Rules: A Critical Analysis of the Impact of "More A--More B" and "Same A--Same B" - Van Dooren, Wim; De Bock, Dirk; Weyers, Dave; Verschaffel, Lieven (Educational Studies in Mathematics, 2006)
In the international community of mathematics and science educators the intuitive rules theory developed by the Israeli researchers Tirosh and Stavy receives much attention. According to this theory, students' responses to a variety of mathematical and scientific tasks can be explained in terms of their application of some common intuitive rules. Two major intuitive rules are manifested in comparison tasks: "More A--more B" and "Same A--same B". In this paper, we address two important questions for which the existing literature on intuitive rules does not provide a convincing research-based answer: (1) are the reasoning processes of students who respond in line with a given intuitive rule actually affected by that rule or by essentially other misconceptions (leading to the same answer), and (2) are individual students consistent in their choice of one of the intuitive rules when confronted with different, conceptually unrelated tasks? A test consisting of five comparison problems from different mathematical subdomains was administered collectively to 172 Flemish students from Grades 10 to 12. An analysis of students' written calculations and justifications suggested that the students were considerably less affected by the intuitive rules than their multiple-choice answers actually suggested. Instead, essentially different misconceptions and errors were found. With respect to the issue of individual consistency, we found that students who made many errors did not answer systematically in line with one of the two intuitive rules.
Keywords: Computation; Foreign Countries; High School Students; Intuition; Mathematical Concepts; Mathematics Education; Mathematics Tests; Misconceptions; Problem Solving; Science Education; Secondary School Mathematics